Outcomes of atherectomy in treating severely calcified coronary lesions in patients with reduced left ventricular ejection fraction: A systematic review and meta-analysis - Abusnina, Waiel; Mostafa, Mostafa Reda; Al-Abdouh, Ahmad; Radaideh, Qais; Ismayl, Mahmoud; Alam, Mahboob; Shah, Jaffer; Yousfi, Noraldeen El; Paul, Timir K.; Ben-Dor, Itsik; Dahal, Khagendra (Frontiers in Cardiovascular Medicine, 2022)
Background: Severely calcified coronary lesions with reduced left ventricular (LV) function result in worse outcomes. Atherectomy is used in treating such lesions when technically feasible. However, there is limited data examining the safety and efficacy of atherectomy without hemodynamic support in treating severely calcified coronary lesions in patients with reduced left ventricular ejection fraction (LVEF). Objective: To evaluate the clinical outcomes of atherectomy in patient with reduced LVEF. Methods: We searched PubMed, Cochrane CENTRAL Register and ClinicalTrials.gov (inception through July 21, 2021) for studies evaluating the outcomes of atherectomy in patients with severe LV dysfunction. We used random-effect model to calculate risk ratio (RR) with 95% confidence interval (CI). The endpoints were in-hospital and long term all-cause mortality, cardiac death, myocardial infarction (MI), and target vessel revascularization (TVR). Results: A total of 7 studies consisting of 2238 unique patients were included in the analysis. The median follow-up duration was 22.4 months. The risk of in-hospital all-cause mortality using atherectomy in patients with severely reduced LVEF compared to the patients with moderate reduced or preserved LVEF was [2.4%vs.0.5%; RR:5.28; 95%CI 1.65–16.84; P=0.005], the risk of long term all-cause mortality was [21% vs.8.8%; RR of 2.84; 95%CI 1.16–6.95; P=0.02] . In-hospital TVR risk was 2.0% vs.0.6% (RR: 4.15; 95%CI 4.15–15.67; P= 0.04) and long-term TVR was[6.0% vs. 9.9%; RR of 0.75; 95%CI 0.39–1.42; P = 0.37]. In-hospital MI was [7.1%vs.5.4%; RR 1.63; 95%CI 0.91–2.93; P=0.10], long-term MI was [7.5%vs.5.7; RR 1.74; 95%CI 0.95–3.18; P = 0.07). Conclusion: Our meta-analysis suggested that the patients with severely reduced LVEF when using atherectomy devices experienced higher risk of clinical outcomes in the terms of all-cause mortality and cardiac mortality. As we know that the patients with severely reduced LVEF are inherently at increased risk of adverse clinical outcomes, this information should be considered hypothesis generating and utilized while discussing the risks and benefits of atherectomy in such high risk patients. Future studies should focus on the comparison of outcomes of different atherectomy devices in such patients. Adjusting for the inherent mortality risk posed by left ventricular dysfunction may be a strategy while designing a study.